Extratos vegetais de cana crua e a atenuação da toxidez por alumínio no crescimento inicial de cana-de-açúcar - Malvestiti, Jacqueline Aparecida (Universidade Federal de São Carlos, 2014)
About 70% of the area cultivated with sugarcane in Brazil are on acid soils, characterized by having severe limitations in terms of fertility. Organic acids from residues decomposition of sugarcane, due to mechanized harvest without the use of fire, are able to interact with elements of the soil solution. This research project was aimed at investigating the influence of the addition of plant extracts residue of sugarcane in the complexation of Al phytotoxic and expansion of the root system of the crop . The experiment was conducted in laboratory and greenhouse, with the following specific objectives: (a) characterize chemically and determine qualitatively and quantitatively the organic acids present in plant extracts of the residue of sugarcane harvested mechanically to select the plant extract with greater neutralizing capacity of Al; (b) test doses of plant extracts of of sugarcane for complexation of toxic Al; (c) determine the depth of root development of varieties of sugarcane under conditions of high Al saturation; (d) verify that the plant extracts applied on columns filled with soil naturally acid, cultivated with sugar cane were able to promote the elevation of the pH of soil. The results of laboratory analyzes of plant extracts showed greater power to carry exchangeable cations along the soil profile and neutralizing Al phytotoxic to the plant extract of the residue variety RB867515. The results of the experiment at home a greenhouse indicated that the varieties of sugarcane differed in Al tolerance of the soil, on the accumulation of biomass and aluminum aerial part and root system, as well as deepening the roots. The plant extract residue of variety RB867515 had a positive effect on root development of varieties, in raise soil pH, alleviating Al toxicity and the availability of basic cations to the sublayers of the soil columns. The dosage of the plant extract, which promoted effective improvement in soil properties, was the equivalent of 21 tha- 1. The varieties were classified as tolerance to Al, as follows : RB966928 > RB855453 > RB867515.
Plant extract from green cane and attenuation of toxic aluminum in initial growth of sugarcane
Keywords: Cana-de-açúcar; Extrato vegetal; Cana-de-açúcar- colheita mecanizada; Toxidez por alumínio; Compostos orgânicos; Plant extracts; Sugarcane; Mechanized harvest; Al toxicity; Organic compounds; CIENCIAS AGRARIAS